2008
DOI: 10.1590/s1519-566x2008000200013
|View full text |Cite
|
Sign up to set email alerts
|

Uso de silício como indutor de resistência em batata a Myzus persicae (Sulzer) (Hemiptera: Aphididae)

Abstract: -The aphid Myzus persicae (Sulzer) is an important pest of potato and causes direct harm, due to the quantity of sap extracted and for being vector of important phytovirus. This work was carried out to evaluate the action of silicon as a resistance inducer of potato to M. persicae. Four treatments were tried: foliar fertilization with silicon acid at 1%; soil fertilization with 250 ml silicic acid solution at 1%; foliar fertilization with silicon acid at 1% + soil fertilization with 250 ml silicic acid solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 25 publications
5
28
0
13
Order By: Relevance
“…Nymphal survival, at least through the 3rd and 4th instars, was not signi icantly different between the two untreated (Table 2). These results are similar to those of Correa et al (2005) who observed a higher nymphal mortality of B. tabaci biotype B after foliar application of silicon on cucumber plants, probably due to an increase in the plants defensive compounds induced by a higher activity of oxidative enzymes (Gomes et al 2008).…”
Section: Nymphal Survivalsupporting
confidence: 90%
See 3 more Smart Citations
“…Nymphal survival, at least through the 3rd and 4th instars, was not signi icantly different between the two untreated (Table 2). These results are similar to those of Correa et al (2005) who observed a higher nymphal mortality of B. tabaci biotype B after foliar application of silicon on cucumber plants, probably due to an increase in the plants defensive compounds induced by a higher activity of oxidative enzymes (Gomes et al 2008).…”
Section: Nymphal Survivalsupporting
confidence: 90%
“…In addition, no effect of silicon on the vegetative development of soybeans was observed; the mean weights found for root and aerial parts, and the root:aerial parts ratio were the same for silicon-treated or untreated (Table 5). Although silicon has been demonstrated not to affect the dry weight of the aerial parts of several plants (Costa et al 2007, Tokura et al 2007, Gomes et al 2008, Smith et al 2008, changes in the root:aerial parts ratio observed in our laboratory tests must be investigated under ield conditions.…”
Section: Eff Ect Of Silicon On the Vegeta Ve Development Of Soybeanmentioning
confidence: 69%
See 2 more Smart Citations
“…Contudo, do ponto de vista fi siológico, para o crescimento e o desenvolvimento das plantas, o silício tem demonstrado efeito benéfi co sobre o aumento de produção de diversas culturas (Gomes et al, 2008). Acredita-se que ele possa interferir na arquitetura das plantas e favorecer a fotossíntese, ao proporcionar folhas mais eretas, que têm maior efi ciência fotossintética.…”
Section: Introductionunclassified